Analisis Formula Cawelti dalam Novel Seijo no Kyūsai Karya Keigo Higashino - Putri, Tiara Rosmika; Anwar, Fithyani; Imelda, Imelda (Universitas Hasanuddin, 2025)
This study examines the application of the classic detective formula in Seijo no Kyūsai by Keigo Higashino using John G. Cawelti’s framework. The research aims to identify narrative patterns and structural variations that distinguish the novel from conventional detective mysteries. Using a descriptive qualitative method with note-taking, the study analyzes data from both the Japanese text and its Indonesian translation. The findings indicate that the novel applies the five aspects of the classic detective formula but modifies them by introducing an impossible crime, thereby creating greater complexity. The crime is revealed not through explicit depiction but through indications of cause of death, while real and false clues emerge from character actions, monologues, and misleading alibis. The investigation integrates police inquiry with scientific experiments by Yukawa Manabu as a nonconventional detective. The solution unfolds gradually through analytical dialogue, ending with the perpetrator’s arrest while leaving emotional tension that enriches the narrative.